Maintaining Bank Customer Loyalty during Covid-19 Pandemic through Promotion, Service Quality and Customer Relationship Management - Fitriani, Nani; Karina, Yuri; Adelina, Raden (Adpebi Science Series, 2022)
Promotion, Service Quality, and Customer Relationship Management are three important factors that define Customer Loyalty. This study was conducted to analyze the influence of promotion, service quality and customer relationship management (CRM) on customer loyalty of PT Bank Central Asia Tbk. in the pandemic era. The research method used is quantitative method, using a questionnaire as a research instrument. The population in this research is customers of PT Bank Central Asia Tbk in Indonesia. The sample consisted of 100 people, chosen using purposive sampling method. The data was processed using the application of IBM SPSS Version 25 to examine the influence of promotion, service quality, and CRM on customer loyalty. The findings reveal that promotion as well as CRM do not have influence on Customer Loyalty. On the other hand, service quality was proven to have influence on Customer Loyalty. Moreover, the result of the F test shows that promotion, service quality, and customer relationship management simultaneously effect customer loyalty.